Validation of a scale of health beliefs about type 1 diabetes for the Mexican context: HBM-T1DM - Citlali Calderón; Lorena Carrete; Jorge Vera (Instituto Nacional de Salud Pública, 2018)
Objective. To generate a scale to measure health beliefs among Mexican adolescents and young people with type 1 diabetes (T1DM) to determine the extent to which they affect adherence to treatment and to be able to develop more effective social marketing campaigns. Materials and methods. Based on the Health Belief Model (HBM), a scale was gener- ated; three field tests were applied, and it was administered in two regions of Mexico to young people with type 1 diabetes. Tests of reliability, stability, convergence-discrimination and predictive validity were developed. Results. The main predictor is perceived barriers to treatment adherence, followed by self-efficacy to disease control, susceptibility/vulnerability to disease complications and perceived benefits of treatment. Conclusion. This scale may be especially useful for better monitoring young Mexican patients with T1DM and prevent sequelae of disease.